A NIR-emissive probe with a remarkable Stokes shift for CO-releasing molecule-3 detection in cells and in vivo. Issue 6 (21st February 2022) - Li, Songjiao; Yang, Ke; Zeng, Jiayu; Xia, Yuqing; Cheng, Dan; He, Longwei
Abstract : A NIR-emitting probe with a remarkable Stokes shift for detecting CO-releasing molecule-3 in living cells and in vivo . Abstract : Carbon monoxide (CO) is regarded as one of the most important gaseous transmitters, playing a vital role in biological systems; meanwhile, abnormal levels of CO can be correlated with conditions such as lung disease, Alzheimer's disease, and cardiovascular disease. CO-releasing molecules (CORMs) are chemical agents used to release CO as an endogenous, biologically active molecule in order to treat diseases. CO-releasing molecule-3 (CORM-3), as a convenient and safe CO donor and therapeutic drug molecule, has been widely used to release exogenous CO in living cells to study the physiological and pathological roles of CO in living systems. Herein, we designed a NIR-emitting probe (NIR-CORM-3 ) with a large Stokes shift based on a 4-(dimethylamino)cinnamaldehyde lepidine derived fluorophore. A 4-nitrobenzyl group was selected as the CORM-3 recognizing moiety, and the probe is able to selectively and sensitively respond to CORM-3 (within only 15 min). Upon encountering CORM-3, NIR-CORM-3 releases a fluorophore with a response at 670 nm, and it shows a remarkable Stokes shift (up to 250 nm). In addition, NIR-CORM-3 has low cytotoxicity and exhibits outstanding NIR imaging abilities in living cells and mice.